Blast and Ballistic Resistance of Ultra-High Strength Steel. Issue 3 (September 2013) - Ma, C.Y.; Liew, J Y Richard
This paper investigates the blast and ballistic resistance of high strength steel XAR-450 with a tensile strength of about 1200 MPa. Compared to normal strength steel, this steel provides significant improvements in ultimate strength performance and can be designed with minimum weight, which are of increasing importance for use in the construction and defense industries. First, material properties of high strength steel are investigated to understand the protective capability and robustness of the proposed protective structures by utilizing the high strength steel plate to resist blast loading and high velocity impact. Both strain hardening and strain rate hardening of XAR-450 steel are investigated. Tensile Split Hopkinson Bar tests were performed to obtain the ultimate tensile strength at strain rates between 10 3 s −1 and 10 4 s −1 . Test results show noticeable increase of tensile strength of up to 40% with the increase of strain rate from static to 10 4 s −1 . Suitable rate-dependent constitutive models and parameters are proposed based on least-squares fitting with test data. The ductile fracture mechanics is also investigated. Thus these material parameters can be used for numerical analysis of protective structures subject to blast and impact. Finally, high velocity impact resistance of high strength steel XAR-450 against bullet and Fragment Simulating Projectile (FSP) were investigated experimentally and numerically. The blast resistance of the high strength XAR-450 steel plate is investigated by the comparison of blast field test result with the finite element analysis results.